Nonintubated thoracic surgery: a lead role or just a walk on part? - Mineo, Tommaso C.; Tacconi, Federico (Chinese Journal of Cancer Research; Vol 26, No 5 (October 31, 2014): Chinese Journal of Cancer Research, 2014)
With the advent of the patient-centered health care concept, thoracic surgeons of the modern era are called to minimize at most the overall invasiveness of their performances, while increasing safety and effectiveness as much as possible. This need has driven an outstanding development of minimallyinvasive surgical approaches, which are now the standard to perform a broad spectrum of thoracic operations. A recent and fascinating evolution in this field is represented by the increasing interest toward the use of so-called “nonintubated” anesthesia protocol, which are expected to provide a further improvement in postsurgical outcomes (1-8).